Talent Management Practices and Employee Performance: Mediation role of Employee Engagement - Gautam, Kishor Kumar (Nepalese Journal of Management Science and Research, 2023)
This study examines the effect of talent management practices on the employee performance of the commercial banks of Nepal. The author examines the mediating effect of employee engagement on the relationship between talent management practices and employee performance. A stratified simple random sampling technique was employed to enable select the respondents from the three strata and data were collected from 300 employees working in Nepalese commercial banks. A structured questionnaire containing standard scales of talent management practices, employee engagement, employee performance, and some demographic variables was used. Harman’s one-factor test was conducted to test the common method biased. Confirmatory factor analysis (CFA), and structural equation modeling approach were used to analyze mediating effect. Three factors, namely talent attraction, talent development, and talent retention were identified as the talent management practices in Nepalese commercial banks, predicting the positive relationship of talent management practice to employee performance. Employee engagement mediates the relationship between talent management practices and employee performance. This study contributes to the resource-based views and social exchange theory and attempts to fulfill the gap in empirical research on personal psychology, human capital/ and organizational management in developing countries.